New Approaches to Developing the Integral Indicator Methodology for Estimating the Financial Efficiency of Agricultural Entities in Poland, the Republic of Moldova, and EU Countries - Mariusz Trojak; Barbara Kiełbasa; Daniela Popa; Aliona Sargo (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2019)
Economic literature pays a great deal of attention to economic and financial efficiency, expressed in terms of competition, concentration, productivity and profitability. This paper provides an all-embracing framework for the various existing theories in this area and illustrates these theories with practical applications. Currently, changing the size of the production potential in agricultural units in the Republic of Moldova depends to a great extent on the influence of different trends in the modification of production resources: the reduction of labor resources and agricultural land, quantitative and qualitative changes in fixed assets, and in current assets, etc. The notion of resource potential means the totality of the volume of all resources (natural, labor, material, intellectual, information, etc.) on specific enterprises, territories, branches, regions. Evaluating a broad field of research, the paper describes profit maximizing food products and demonstrates how several widely-used products can be fit into this framework. The authors also present an overview of the current major trends in the food sector and relate them to the assumptions for food products, thereby displaying their relevance and timeliness. The results include a set of recommendations for future research on this topic. The design, methodology and approach of this research is to explain why efficiency can help obtain a profit surplus, and to measure this efficiency. For quality of methodology we apply a range of statistical methods, as well as the strategic capability of organisations – made up of resources and competences. One way to approach the stategic capability of an organisation is to consider its strengths and weaknesses (for example, where it has a competitive advantage, profit, efficiency or disadvantage). Based on our research and results, we sought to understand the concepts of financial effciency and to apply these concepts to practical situations. At the start of each analysis entrepreneurship plays an important role. Most organisations have to innovate constantly to obtain profit and efficiency for food products. They need to be first into a market, or simply a follower of customers in developing new products and services. Original studies in Moldova and Poland regarding farm concentration in terms of Gini Coefficient, Gini Index and Concentration Index of the utilized agricultural area. Original calculus formula to determine the Concentration Index of the UAA for the top 10% largest farms in Moldova and UK.